A qualitative inquiry of the adoption, economic impact, and implications of virtual tourism to game parks within Limpopo and Mpumalanga Provinces of South Africa - Fourie, Sonja (University of Pretoria, 2023)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2022.